THE IMPACT OF MIGRATION SECURITIZATION ON THE INCREASE OF ISLAMOPHOBIA-BASED ATTACKS IN THE UNITED STATES IN 2015-2019 - Victoriana Melati (Indonesian Association for International Relations, 2020)
This paper will discuss the United States policy under Donald Trump's administration which places migration as an agenda of securitization by restricting immigrants from entering the United States, especially Muslim immigrants. Trump firmly said to reject the entry of immigrants from six Muslim countries, namely Chad, Iran, Libya, Syria, Somalia and Yemen. Trump also added that the ban on the entry of immigrants was also applied to Venezuelans and North Koreans. The step was taken by Trump with the aim of ensuring the security of the United States from various threats potentially brought by the immigrants. Then, this paper will answer the big questions about how securitization of migration affected the emergence of Islamophobia in the United States. In analyzing these problems, we use the concept of securitization of migration with four operational variables, namely: 1. Framing by speech acts, 2. Politicization of fear, 3. The impacts (positive and negative): Securitization policy and the islamophobia actions. The results of this study indicate that securitization of migration process has an impact on the increasing actions of Islamophobia-based in the United States. Keywords: Securitization of Migration, Travel Ban Policy, Islamophobia, United States